KOMPETENSI PROFESIONAL GURU PAI DALAM MEMANFAATKAN GOOGLE CLASSROOM - Ahmad Muhajir; Muslimah Muslimah; Muzakki Muzakki (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2022)
The purpose of this study was to identify the professional competence of Islamic Education teachers in utilizing google classroom. Researchers used this type of library research by examining data from sources related to research problems in the form of textbooks, scientific journals, e-books, and sources related to the professional competence of Islamic Education teachers. The findings of the study show that a professional competent Islamic Education teacher must be able to master all kinds of things related to Islamic Education learning, both in terms of material, strategy, evaluation and being able to develop Islamic Education learning media. The professional competences that must be possessed by a teacher are pedagogical, social, personal and professional competencies. Meanwhile, to improve the ability of Islamic Education teachers in the field of technology can use learning media, for example by using the google classroom application. By utilizing these learning media, it is hoped that the teacher can develop PAI learning media that is not only done face-to-face but also online, so that it can have a good impact to strengthen the relationship between teacher and students.